2005
DOI: 10.1063/1.1858872
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic of the self-healing of metallized polypropylene film by modeling of the broadening emission lines of aluminum emitted by plasma discharge

Abstract: Metallized-film capacitors have the property, even under high continuous voltage, to self-heal i.e., to clear a defect in the dielectric. The self-healing process is a consequence of a transient arc discharge. It has been previously shown that during the discharge, due to Joule effect, the metal is vaporized until the arc extinguishes. The discharge duration has been found to be inversely proportional to the mechanical pressure applied on the layers of metallized films making up a capacitor. The aim of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 21 publications
0
51
0
Order By: Relevance
“…Polymer capacitors, because of their high breakdown strength and graceful failure mode, are very attractive for these applications [4][5][6]. Recently, we reported that in defects modified polyvinylidene fluoride (PVDF) based polymers such as P(VDF-CTFE) (CTFE: chlorotrifluoroethylene) and P(VDF-HFP) (HFP: hexafluoropropylene), in which the dielectric constant can be tailored to avoid the "early" electric displacement saturation, a very high electrical energy density can be obtained [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Polymer capacitors, because of their high breakdown strength and graceful failure mode, are very attractive for these applications [4][5][6]. Recently, we reported that in defects modified polyvinylidene fluoride (PVDF) based polymers such as P(VDF-CTFE) (CTFE: chlorotrifluoroethylene) and P(VDF-HFP) (HFP: hexafluoropropylene), in which the dielectric constant can be tailored to avoid the "early" electric displacement saturation, a very high electrical energy density can be obtained [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The electrode materials locally evaporate, or self-clear, around defects during highvoltage breakdown. [7][8][9] Metallic films are not sufficiently compliant for the dielectric elastomers. To enhance the compliancy of metallic electrodes, zig-zag shaped metallic lines were used to obtain 80 % area strains.…”
mentioning
confidence: 99%
“…Resonance, Stark, and van der Waals broadening can be calculated in the impact approximation, which is valid when the collision time is much shorter than the time between collisions, 10,11 …”
Section: Line Broadeningmentioning
confidence: 99%
“…This approximation assumes that the radiating particles are perturbed by a slowly varying potential field which can be considered quasistatic. This approximation results in a Levy profile, 10,14 …”
mentioning
confidence: 99%